Appraisal of purple coneflower (Echinacea purpurea) extract on production performance, internal organs, and gut microflora of japanese quail (Acta Scientiarum. Animal Sciences, 2017)
An experiment was carried out to evaluate the effects of Echinacea purpurea (EP) extract at 5 levels (0, 0.25, 0.5, 1 or 2 mL L-1 of drinking water) on performance, internal organs and gut microflora of Japanese quail (Coturnix coturnix Japonica). The results showed that EP extract decreased feed intake and body weight gain of quails. The feed conversion ratio of quails fed with EP extract at the level of 0.5 ml L-1 drinking water was significantly decreased compared to the control group. Adding EP extract at the levels of 0.25, 0.5 or 1 mL L-1 drinking water decreased carcass yield of the birds (p < 0.05). The relative weight of internal organs of the birds fed different levels of EP extract was not significantly different. Birds consumed EP extract at the levels of 1 or 2 mL L-1 drinking water had lower ileal aerobic bacteria population compared to the control group; however, the ileal Coliform population increased by EP extract supplementation (p < 0.05). Results of the present study indicated that using EP extract at the level of 0.5 mL L-1 drinking water could improve feed conversion ratio of quails; however, it decreased the carcass yield of the birds.